Ali je naravna členitev prostora lahko izhodišče za načrtovanje in urejanje prostora? - Marušič, Janez (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2005)
Regionalization as an activity that splits a landscape into units can be carried out differently according to the planning procedures used. The naturallandscape units are connected to the planning of natural resource, which were the content of landscape at its very beginning. The arbitrary defined landscape units, i.e. raster pixels can be considered as a type of spatialunit that may surmount the two opposing types of landscape units.
Keywords: prostor; pokrajina; Subdivisions of the Kingdom of Yugoslavia; regije; regionalno planiranje; prostorsko planiranje; spatial planning; prostorski razvoj; strategija; Slovenia; Slovenija